Challenges of Monitoring Blood Levels of Bedaquiline in Drug-Resistant Tuberculosis: A Narrative Review - Nur Isra; Santi Purna Sari; Yahdiana Harahap; Raden Rara Diah Handayani (Green Publisher Indonesia, 2025)
Bedaquiline, a second-line drug for drug-resistant tuberculosis (MDR-TB), is one of the latest generation drugs in the treatment of tuberculosis (TB). However, the challenge in determining the optimal dose and individual pharmacokinetic variability requires the implementation of Therapeutic Drug Monitoring (TDM). This article aims to evaluate the challenges of TDM bedaquiline through a narrative review of the current literature. Relevant articles were identified through computerized searches on PubMed and Google Scholar using a combination of keywords related to bedaquiline, pharmacokinetics, and TDM. Limited clinical data indicate a lack of standard exposure targets and reliable efficacy thresholds. Pharmacokinetic variability is influenced by factors such as age, weight, gender, genetics, comorbidities, and serum albumin. Technical challenges include the need for precise analytical methods and the accessibility of technology in clinical practice. The use of TDM for bedaquiline offers the potential to improve the efficacy of MDR-TB treatment, but more research is needed to address pharmacokinetic variability and develop standardized guidelines.